Completing the canvas: advances and challenges for DNA-PAINT super-resolution imaging - van Wee, Raman (Trends Biochem Sci, 2021)
Single-molecule localization microscopy (SMLM) is a potent tool to examine biological systems with unprecedented resolution, enabling the investigation of increasingly smaller structures. At the forefront of these developments is DNA-based point accumulation for imaging in nanoscale topography (DNA-PAINT), which exploits the stochastic and transient binding of fluorescently labeled DNA probes. In its early stages the implementation of DNA-PAINT was burdened by low-throughput, excessive acquisition time, and difficult integration with live-cell imaging. However, recent advances are addressing these challenges and expanding the range of applications of DNA-PAINT. We review the current state of the art of DNA-PAINT in light of these advances and contemplate what further developments remain indispensable to realize live-cell imaging.